2014
DOI: 10.1021/jf501329y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antioxidant Capacities, α-Dicarbonyls, and Phenolic Phytochemicals in Florida Varietal Honeys Using HPLC-DAD-ESI-MSn

Abstract: Honeys contain phenolic compounds and α-dicarbonyls with antioxidant and antimicrobial capacities, respectively. The type and concentration of these compounds vary depending on the floral source and geographical location where the honey is produced. Seventeen varietal honeys, including 12 monofloral and 5 multifloral honeys, were sampled from different regions of Florida. The monofloral honeys included those from citrus, tupelo, palmetto, and gallberry. These honeys were evaluated for their antioxidant capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 57 publications
(156 reference statements)
3
45
2
Order By: Relevance
“…Indeed, the highest amount of TF was measured in dill honey, while according to other studies (Tenore et al, 2012) almond honey by the Sicilian black bee contains high amounts of quercetin (2.35 mg/100 g honey). On the other hand, the eucalyptus and manuka honeys show around one half TF than dill honey (Table 1), whereas their small amounts of quercetin (0.3–0.5 mg/100 g honey), luteolin (0.3–0.4 mg/100 g honey) and kaempferol (0.13–0.17 mg/100 g manuka honey; 0.05–0.07 mg/100 g eucalyptus honey) (Marshall et al, 2014; Martos et al, 2000a; Yao et al, 2003) are possibly responsible for iron-chelating properties (Ren et al, 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the highest amount of TF was measured in dill honey, while according to other studies (Tenore et al, 2012) almond honey by the Sicilian black bee contains high amounts of quercetin (2.35 mg/100 g honey). On the other hand, the eucalyptus and manuka honeys show around one half TF than dill honey (Table 1), whereas their small amounts of quercetin (0.3–0.5 mg/100 g honey), luteolin (0.3–0.4 mg/100 g honey) and kaempferol (0.13–0.17 mg/100 g manuka honey; 0.05–0.07 mg/100 g eucalyptus honey) (Marshall et al, 2014; Martos et al, 2000a; Yao et al, 2003) are possibly responsible for iron-chelating properties (Ren et al, 2008). …”
Section: Resultsmentioning
confidence: 99%
“…However, the type and concentration of these compounds are known to vary depending on geographical location and floral source. Manuka honey produced in New Zealand contains large amount of quercetin and kaempherol compared with other species of honey [22] . Previous studies reported that quercetin inhibited a decrease in BMD in OVX mice, and quercetin suppressed the RANKL-induced NFATc1 expression and osteoclast formation in RAW264.7 cells [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, kaempherol inhibited interleukin-1β-stimulated, RANKL-mediated osteoclastogenesis via downregulation of NFATc1 in mouse bone marrow cells [24] . In addition, manuka honey is also rich in luteolin [22] , which has a preventive effect of OVX-induced bone loss and inhibition of osteoclast formation in RAW264.7 cells [25] . Thus, polyphenols such as quercetin, kaempherol, and luteolin in the manuka honey could also have contributed to suppression of bone resorption in OVX mice.…”
Section: Discussionmentioning
confidence: 99%
“…Honey can be considered as one of the oldest, or even the oldest wound dressing known by humans. Honey was used as wound dressing in ancient Egypt (>1500 BC), described by Hippocrates (460-377 BC) and used throughout the Middle Ages 43,44 .…”
Section: Medical Honey: No Longer So Alternativementioning
confidence: 99%
“…Eleven were assessed as being at unclear risk of bias [40][41][42][43][44][45][46][47][48][49][50] , and all remaining studies were assessed as being at overall high risk of bias. Details on quality assessment are presented in Fig.…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%